2012
DOI: 10.1108/17566261211264172
|View full text |Cite
|
Sign up to set email alerts
|

Exploring gender differences in attitudes of university students towards entrepreneurship

Abstract: Entrepreneurship AbstractPurpose -The purpose of this paper is to understand gender differences in entrepreneurial intentions as measured by perceived feasibility and perceived desirability, and to explore gender differences in perceptions of entrepreneurship education needs -in terms of programmes, activities or projects -to succeed in an entrepreneurial career from the university students' point of view.Design / Methodology /Approach -Using data gathered from 3420 university students in more than 10 countrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
102
1
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 129 publications
(124 citation statements)
references
References 50 publications
6
102
1
8
Order By: Relevance
“…C. C. Baughn, Chua, & Neupert, 2006;Brush, Bruin, & Welter, 2009;Ettl & Welter, 2010). Yet research suggests that female entrepreneurs face more challenges and barriers than their male counterparts (Al Gharaibeh, 2011;Caputo, Mehtap, Pellegrini, & Al-Refai, 2015;S Carter, Anderson, & Shaw, 2001;Dabic, Daim, Bayraktaroglu, Novak, & Basic, 2012;Jamali, 2009;Ramadani, Hisrich, & Gërguri-Rashiti, 2015;Ramadani, 2015). This is expected to be even more prevalent in conservative and patriarchal societies like those in the Middle East, where Islam plays a dominant role in the governance of society (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…C. C. Baughn, Chua, & Neupert, 2006;Brush, Bruin, & Welter, 2009;Ettl & Welter, 2010). Yet research suggests that female entrepreneurs face more challenges and barriers than their male counterparts (Al Gharaibeh, 2011;Caputo, Mehtap, Pellegrini, & Al-Refai, 2015;S Carter, Anderson, & Shaw, 2001;Dabic, Daim, Bayraktaroglu, Novak, & Basic, 2012;Jamali, 2009;Ramadani, Hisrich, & Gërguri-Rashiti, 2015;Ramadani, 2015). This is expected to be even more prevalent in conservative and patriarchal societies like those in the Middle East, where Islam plays a dominant role in the governance of society (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Contrarily, they also believe that managing a business may be overwhelming, and starting a business in a former transition economy can be riskier due to problems related to financing and later to a successive internationalisation process (Dabić et al, 2012). For the gender issue, differences in the propensity toward entrepreneurship between male and female still persist; male are still more positive about entrepreneurship, although this difference is decreasing in the last years (Dabic et al, 2012); a matter that has also been found in other contexts (e.g. Ramadani et al, 2015).…”
Section: Context Of Research: Evidence From Croatiamentioning
confidence: 88%
“…While the significant risks posed by internal political stability are no longer of a concern, entrepreneurs in Croatia still struggle with lack of financing, a heavily reliance on export and risks related to variability in legal environment as the most relevant threats to their regular operations (Bublic et al, 2013). In particular, as also found in other transition economies (Iakovleva and Solesvik;2014), lack of knowledge on how to finance a start-up firm has been identified as one of most relevant problems hampering the growth of a new entrepreneurial venture (Dabic et al, 2012;Ramadani et al, 2015).…”
Section: Context Of Research: Evidence From Croatiamentioning
confidence: 99%
See 2 more Smart Citations